Perfil de competencias del profesional que cumple funciones de monitoreo, evaluación y gestión de evidencias de programas y proyectos de desarrollo. Un aporte para las decisiones basadas en evidencias - Miranda, Eva (2015)
Programs and development projects that are part of public policies need to be efficient in investment and effective in achieving objectives and results. Monitoring and evaluation (ME) are strategic and systematic functions that seek to generate rigorous and reliable information on effects of programs and development projects. There is consensus about the need to develop capacity and professionalize ME, to adopt common standards, and to strengthen national development strategies. This should result in better public policies, evaluations, which should support sustainable development with equity and inclusion. In our country, public social and budget programs, as well as programs and projects funded by international agencies require ME systems to obtain rigorous evidence on outcomes. They should be reflected in both budget allocation and in the improvement of processes and strategies. This article identifies specific functions of ME professionals, and proposes a profile of skills, attitudes and knowledges and specific competencies. A validated profile is presented as a contribution for results-based management and evidence-based decision making, and for its implementation in processes and systems related to human resources and ME management. It is a tool to be used primarily in planning and provision, work organization, capacity development and compensation. It is a pioneering experience in the country, and it is available for academic and governmental institutions or other actors involved in ME services.